Effects of essential oils, ionophore and live yeast supplementation on rumen fermentation dynamics in Jersey cows - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2015)
Dissertation (MScAgric)--University of Pretoria, 2014.